2010
DOI: 10.1021/ja1046704
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Fast Proton Transport along One-Dimensional Water Chains Confined in Carbon Nanotubes

Abstract: A reactive molecular dynamics simulation employing the multistate empirical valence bond (MS-EVB) methodology is reported for the hydration structure of an excess proton in a (6,6) carbon nanotube as well as for the mechanism of proton transport (PT) within the nanoconfined environment. The proton is found to be hydrated in a distorted Zundel cation (H(5)O(2)(+)) form within the one-dimensional, confined water chain. Proton transfer events occur via a "Zundel-Zundel" mechanism through a transient H(7)O(3)(+) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
165
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(179 citation statements)
references
References 21 publications
14
165
0
Order By: Relevance
“…For instance, compared with K + conductance that requires physical diffusion, proton transport could be much more efficient based on an orientational hydrogen-bonding defect mechanism 50,51 . Here the observed K + /Na + selectivity can be understood based on conclusions from previous MD simulations 48,49 , which demonstrates that the free-energy costs of constraining hydrated K + within a sub-nm pore are notably less than those of hydrated Na + .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, compared with K + conductance that requires physical diffusion, proton transport could be much more efficient based on an orientational hydrogen-bonding defect mechanism 50,51 . Here the observed K + /Na + selectivity can be understood based on conclusions from previous MD simulations 48,49 , which demonstrates that the free-energy costs of constraining hydrated K + within a sub-nm pore are notably less than those of hydrated Na + .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, ion channels present the greatest challenges and opportunities: Their narrow pores are usually hydrated; thus, channel blockers effectively have to displace these pore waters. Particularly compelling in this regard are proton channels, such as the M2 proton channel of influenza A virus and Hv1, because waters represent the vehicle with which to achieve proton conduction (91)(92)(93)(94)(95)(96). Notably, in the case of M2, the drug amantadine and other hydrophobic scaffolds were shown to displace clusters of hydrogenbonded waters from main hydration sites (52,54).…”
Section: S1mentioning
confidence: 99%
“…Recently, a work based on multi-state empirical valence bond (EVB) calculations on PT in one-dimensional water chains confined in carbon nanotubes confirmed early results from Hummer et al [29] and revealed that the rate of PT inside the tubes was one order of magnitude faster than in bulk. [28] On the other hand, ab-initio molecular dynamics simulations of water inside nanotube channels [29][30][31] have revealed different mobilities for hydroxide and hydronium ions inside the tubes, depending on the size of the tube and the degree of functionalization of the tube walls. A very recent work [32] reports proton transfer within graphene layers when surrounded by water.…”
Section: Introductionmentioning
confidence: 99%